Communicating assemblies of biomimetic nanocapsules. Issue 26 (24th June 2021) - Zhou, Hongda; Huang, Haowei; Bahri, Mounib; Browning, Nigel D.; Smith, James; Graham, Michael; Shchukin, Dmitry
Abstract : The assemblies of biomimetic nanocapsules can exhibit self-regulating, self-organization functionalities involving internal modulation of self-controlled release by the dynamic stimuli-response-communication-decide-response behaviour. Abstract : Communication assemblies between biomimetic nanocapsules in a 3D closed system with self-regulating and self-organization functionalities were demonstrated for the first time. Two types of biomimetic nanocapsules, TiO2 /polydopamine capsules and SiO2 /polyelectrolytes capsules with different stimuli-responsive properties were prepared and leveraged to sense the external stimulus, transmit chemical signaling, and autonomic communication-controlled release of active cargos. The capsules have clear core–shell structures with average diameters of 30 nm and 25 nm, respectively. The nitrogen adsorption–desorption isotherms and thermogravimetric analysis displayed their massive pore structures and encapsulation capacity of 32% of glycine pH buffer and 68% of benzotriazole, respectively. Different from the direct release mode of the single capsule, the communication assemblies show an autonomic three-stage release process with a "jet lag" feature, showing the internal modulation ability of self-controlled release efficiency. The control overweight ratios of capsules influences on communication-release interaction between capsules. The highest communication-release efficiency (89.6% of benzotriazole) was achieved when the weight ratio of TiO2 /polydopamine/SiO2 /polyelectrolytes capsules was 5 : 1 or 10 : 1. Communication assemblies containing various types of nanocapsules can autonomically perform complex tasks in a biomimetic fashion, such as cascaded amplification and multidirectional communication platforms in bioreactors.